ANALISA PENYEBAB RUSAKNYA CARGO OIL PUMP GUNA MENUNJANG DISCHARGE CARGO PERTAMAX DI ATASKAPAL MT. PATRA TANKER 2 - Wahyu Permana Aji; Eka Darmana (UNIMAR AMNI Semarang, 2021)
When discharging the Pertamax cargo at the port at 10:25 a.m. local time, the on-duty engineer received information from the cargo control room that a problem had occurred, the engineer immediately went to the cargo pump room to check the condition of the cargo oil pump. The engineer is see a leak in the pump room which causes the pump room to be full of spills of Pertamax oil transported by the ship. This research is based on a case study on the ship MT. Patra Tanker 2. The data collection method was carried out by direct observation on the ship for one year and then conducted discussions and interviews with the ship's crew responsible for the cargo pump, as well as data from literature such as instruction manuals and standard operational procedures (SOP). The analysis approach was carried out in a descriptive qualitative manner based on data and various literatures used as a reference or comparison. From the results of the analysis it is stated that the cause of the damage to the cargo oil pump is due to the influence of the quality of the mechanical seal that does not meet the standard, the ball bearing is damaged or worn on the cargo oil pump, the ceramic sleeve shaft (bushing) is thinning or worn, and damage to the cargo oil pump shaft. The cause of damage to the cargo oil pump can be avoided by carrying out routine maintenance and controlling it regularly when the cargo oil pump is running.